Effect of the Community-based SPARSH Program on Control of Selected NCDs: Mixed Methods Evaluation. - Chaudhari, Dhara; Dongre, Amol R.; Shinde, Mayur K.; Deshmukh, Pradeep R. (Indian Journal of Community Medicine)
Background: In community settings, lack of availability of care, nonadherence to medication, high cost of treatment, and poor outcomes of treatment are the core problems in noncommunicable disease (NCD) management. Is there an effect of the community-based SPARSH program on treatment adherence, treatment expenditure, and control among selected NCDs? What are the reasons for low treatment adherence to treatment from patients' point of view? Methodology: It was a community-based explanatory type of mixed method evaluation design, where major quantitative (cross-sectional survey) design followed a minor qualitative (free list) component. A representative sample of 850 NCD patients were selected by two-stage cluster sampling. Structured interviews were done to collect information on history of tobacco and alcohol consumption, treatment adherence, measurement of obesity, blood sugar, and blood pressure levels among known NCD patients. A directed acyclic graph was developed, and path analysis was performed using STATA software. Free list was done with patients who were found to have low adherence to treatment. The study was approved by the Institutional Ethics Committee. Results: As revealed from path analysis, NCD patients enrolled in the SPARSH program had better treatment adherence, which ultimately led to control of hypertension and diabetes.: Ninety percent of patients enrolled in SPARSH had high adherence to treatment, and 90% of them had control in their NCD status. Patients with low adherence to medication reported three major reasons for it: 1) forgetting to take the medicines due to a busy schedule , 2) lack of money to purchase medicines , and 3) feeling better, so felt not necessary to take medicines. Conclusion: The SPARSH program was found to be effective to control hypertension and diabetes among enrolled patients for its services by improving treatment adherence among them. The key strategy of the program based on home visits to patients, counseling, and doorstep delivery of prescribed medication through trained village health workers contributed to treatment adherence and control status.